Hypoactivation in right inferior frontal cortex is specifically associated with motor response inhibition in adult ADHD. Issue 10 (13th May 2014) - Morein‐Zamir, Sharon; Dodds, Chris; van Hartevelt, Tim J.; Schwarzkopf, Wolfgang; Sahakian, Barbara; Müller, Ulrich; Robbins, Trevor
Abstract Adult ADHD has been linked to impaired motor response inhibition and reduced associated activation in the right inferior frontal cortex (IFC). However, it is unclear whether abnormal inferior frontal activation in adult ADHD is specifically related to a response inhibition deficit or reflects a more general deficit in attentional processing. Using functional magnetic resonance imaging, we tested a group of 19 ADHD patients with no comorbidities and a group of 19 healthy control volunteers on a modified go/no‐go task that has been shown previously to distinguish between cortical responses related to response inhibition and attentional shifting. Relative to the healthy controls, ADHD patients showed increased commission errors and reduced activation in inferior frontal cortex during response inhibition. Crucially, this reduced activation was observed when controlling for attentional processing, suggesting that hypoactivation in right IFC in ADHD is specifically related to impaired response inhibition. The results are consistent with the notion of a selective neurocognitive deficit in response inhibition in adult ADHD associated with abnormal functional activation in the prefrontal cortex, whilst ruling out likely group differences in attentional orienting, arousal and motivation. Hum Brain Mapp 35:5141–5152, 2014. © 2014 The Authors. Human Brain Mapping Published by Wiley Periodicals, Inc.